ANALISIS PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP AKSEPTOR KELUARGA BERENCANA PADA TIAP KABUPATEN/KOTA DI PROVINSI BANTEN - Amalia Romadhona (Jurnal Ekonomi-Qu, 2019)
This research aims to analyze the impact of fertile age couples (FEA), per capita expenditure and school participation rates (SPR) on family planning acceptors in districts /cities in Banten Province. This research uses secondary data during the periods of 2011-2017. The research methodology used in this study is panel data regression with FEM (Fixed Effect Model). The results of this research show that simultaneously, FEA, per capita expenditure and SPR have significant impact on family planning acceptors. Partially, FEA and per capita expenditure have significant positive impact on family planning acceptors. Meanwhile, SPR does not have a significant impact on family planning acceptors.